Enhancing Weak-Signal Carrier Phase Tracking in GNSS Receivers. (23rd November 2015) - Curran, James T.
Abstract : Examining the performance of the GNSS PLL, this paper presents novel results describing the statistical properties of four popular phase estimators under both strong- and weak-signal conditions when subject to thermal noise, deterministic dynamics, and typical pedestrian motion. Design routines are developed which employ these results to enhance weak-signal performance of the PLL in terms of transient response, steady-state errors, and cycle-slips. By examining both single and data-pilot signals, it is shown that appropriate design and tuning of the PLL can significantly enhance tracking performance, in particular when used for pedestrian applications.